Treatment of Necrotic Teeth by Apical Revascularization: Meta-analysis. Issue 1 (December 2017) - He, Ling; Zhong, Juan; Gong, Qimei; Kim, Sahng; Zeichner, Samuel; Xiang, Lusai; Ye, Ling; Zhou, Xuedong; Zheng, Jinxuan; Liu, Yongxing; Guan, Chenyu; Cheng, Bin; et al.
Abstract Each year 5.4 million children and adolescents in the United States suffer from dental infections, leading to pulp necrosis, arrested tooth-root development and tooth loss. Apical revascularization, adopted by the American Dental Association for its perceived ability to enable postoperative tooth-root growth, is being accepted worldwide. The objective of the present study is to perform a meta-analysis on apical revascularization. Literature search yielded 22 studies following PRISMA with pre-defined inclusion and exclusion criteria. Intraclass correlation coefficient was calculated to account for inter-examiner variation. Following apical revascularization with 6- to 66-month recalls, root apices remained open in 13.9% cases (types I), whereas apical calcification bridge formed in 47.2% (type II) and apical closure (type III) in 38.9% cases. Tooth-root lengths lacked significant postoperative gain among all subjects (p = 0.3472) or in subgroups. Root-dentin area showed significant increases in type III, but not in types I or II cases. Root apices narrowed significantly in types II and III, but not in type I patients. Thus, apical revascularization facilitates tooth-root development but lacks consistency in promoting root lengthening, widening or apical closure. Post-operative tooth-root development in immature permanent teeth represents a generalized challenge to regenerate diseased pediatric tissues that must grow to avoid organ defects.